ROOT CANAL TREATMENT CAN SAVE INFECTED TOOTH FROM BEING EXTRACTED - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
KUBANG KERIAN, KELANTAN, 10 June 2016 – When bacteria (germs) invade the centre of a tooth called the root canal system which is filled with soft dental pulp made up of nerves and blood vessels, it causes severe pain and/or swelling to the tooth, to the point where the pain becomes unbearable and the only solution seems to be to have the infected tooth removed.